Edukasi Efektivitas Pelaporan Keuangan untuk Optimalisasi Keuangan UMKM di Ciputat - Rahmah, Saskia Auliya; Triyana, Mimi; Pradisa, Riska; Maulana, Muhamad Firman; Winardi, Agung; Widiyati, Dian (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
The Community Service Program (PKM) titled “Financial Reporting Effectiveness Education for Optimizing MSME Financial Management in Ciputat” aims to enhance the ability of micro, small, and medium enterprises (MSMEs) to prepare and utilize financial reports effectively. The main issue faced by MSME actors in Ciputat is the low understanding of financial recording and reporting, which affects cash flow control and business decision-making. The program was carried out through several stages, including data collection, training, mentoring, and evaluation. The training focused on preparing income statements, cash flow reports, and simple balance sheets suited to the participants’ business characteristics, while mentoring ensured optimal application of the materials. The results show a significant improvement in participants’ ability to compile financial reports systematically and use them for business evaluation. Furthermore, the activity encouraged more disciplined and transparent financial recording practices. Although differences in digital literacy remain a challenge, the program has had a positive impact on strengthening financial management capacity and enhancing MSME competitiveness in Ciputat.